A Risk Assessment Tool for Identifying Osteoporosis in Older Women with Type 2 Diabetes Mellitus - Pan, Fenghui; Cui, Wenxia; Gao, Lei; Shi, Xiaoting; Zhang, Mingrui; Li, Man; Yang, Haiyan; Hu, Yun (Experimental and Clinical Endocrinology & Diabetes, 2021)
Purpose To develop a simple and clinically useful assessment tool for osteoporosis in older women with type 2 diabetes mellitus (T2DM).Methods A total of 601 women over 60 years of age with T2DM were enrolled in this study. The levels of serum sex hormones and bone metabolism markers were compared between the osteoporosis and non-osteoporosis groups. The least absolute shrinkage and selection operator regularization (LASSO) model was applied to generate a risk assessment tool. The risk score formula was evaluated using receiver operating characteristic analysis and the relationship between the risk score and the bone mineral density (BMD) and T-value were investigated.Results Serum sex hormone-binding globulin (SHBG), cross-linked C-telopeptide of type 1 collagen (CTX), and osteocalcin (OC) were significantly higher in the osteoporosis group. After adjustment for age and body mass index (BMI), SHBG was found to be correlated with the T-value or BMD. Then, a risk score was specifically generated with age, BMI, SHBG, and CTX using the LASSO model. The risk score was significantly negatively correlated with the T-value and BMD of the lumbar spine, femoral neck, and total hip (all P<0.05).Conclusion A risk score using age, BMI, SHBG, and CTX performs well for identifying osteoporosis in older women with T2DM.
Keywords: osteoporosis; T2DM; LASSO; sex hormones; bone turnover markers